PENGARUH MEDIA DIGITAL WORDWALL BERBANTUAN KOTAK MISTERI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS III SDN 101 PALEMBANG - Nindyta Aurel Salsabila Ar; Aryaningrum, Kiki; Utomo, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low learning outcomes in IPAS at SD Negeri 101 Palembang are presumed to be caused by the continued use of conventional teaching methods in classroom learning. This study aimed to determine the effect of Wordwall digital media assisted by a mystery box on students’ learning outcomes in the IPAS subject for third-grade students at SD Negeri 101 Palembang. This research employed a quantitative method using a Quasi-Experimental Design in the form of a Posttest-Only Control Group Design. The population consisted of all third-grade students at SD Negeri 101 Palembang, totaling 57 students. The sample comprised Class III A as the experimental group with 28 students and Class III B as the control group with 29 students. Data were collected through tests, observations, and documentation. The research instrument consisted of 15 multiple-choice questions that had been tested for validity and reliability, resulting in 12 valid items used as the posttest. Data were analyzed using the Independent Sample T-Test. The results showed that the mean posttest score of the experimental group was 86.64, while that of the control group was 72.86. Statistical testing revealed a significance value (2-tailed) of 0.000 < 0.05 and a t-value of 18.870 > t-table value of 2.004, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the use of Wordwall digital media assisted by a mystery box had a significant effect on students’ learning outcomes in the IPAS subject for third-grade students at SD Negeri 101 Palembang. The contribution of this study lies in the integration of Wordwall digital media and a mystery box as a gamification-based learning innovation that has proven effective in improving elementary school students’ IPAS learning outcomes and can serve as an interactive and engaging learning medium for teachers.